Bitcoin Asset Preference in Mutual Fund Portfolio: A Phenomenological Study - Dwi Ramadana, Novian; Sumiati, Sumiati; Champaca, Mychelia (FIA UB, 2026)
This research examines Indonesian investment managers' attitudes and knowledge toward Bitcoin as an institutional investable asset and reviews the digital asset's worldwide adoption. Indonesian investment managers' role in this job market crisis can be understood through a prudent behaviour mindset, driven by regulatory uncertainty, fiduciary obligations, and risk aversion, even though big global financial houses have already adopted Bitcoin through regulated instruments such as Exchange Traded Funds (ETFs). Using a phenomenological research approach, the study explores the meanings and lived experiences of the strategic leaders of the Indonesian Investment Managers Association (AMII). The results demonstrate that managers are aware of Bitcoin's diversification benefits but prefer asset-backed tokenisation and conventional financial instruments due to concerns about volatility, the market's maturity, and the lack of legal recognition of crypto assets as securities. This study adds to the literature on behavioral finance by exposing loss aversion and status quo bias in developing markets, and it offers policy and industry implications for facilitating judicious digital asset innovation.